Zoonotic spillover and viral mutations from low and middle-income countries: improving prevention strategies and bridging policy gaps - Haq, Zulfqarul; Nazir, Junaid; Manzoor, Tasaduq; Saleem, Afnan; Hamadani, H.; Khan, Azmat Alam; Saleem Bhat, Sahar; Jha, Priyanka; Ahmad, Syed Mudasir (PeerJ, 2024)
The increasing frequency of zoonotic spillover events and viral mutations in low and middle-income countries presents a critical global health challenge. Contributing factors encompass cultural practices like bushmeat consumption, wildlife trade for traditional medicine, habitat disruption, and the encroachment of impoverished settlements onto natural habitats. The existing “vaccine gap” in many developing countries exacerbates the situation by allowing unchecked viral replication and the emergence of novel mutant viruses. Despite global health policies addressing the root causes of zoonotic disease emergence, there is a significant absence of concrete prevention-oriented initiatives, posing a potential risk to vulnerable populations. This article is targeted at policymakers, public health professionals, researchers, and global health stakeholders, particularly those engaged in zoonotic disease prevention and control in low and middle-income countries. The article underscores the importance of assessing potential zoonotic diseases at the animal-human interface and comprehending historical factors contributing to spillover events. To bridge policy gaps, comprehensive strategies are proposed that include education, collaborations, specialized task forces, environmental sampling, and the establishment of integrated diagnostic laboratories. These strategies advocate simplicity and unity, breaking down barriers, and placing humanity at the forefront of addressing global health challenges. Such a strategic and mental shift is crucial for constructing a more resilient and equitable world in the face of emerging zoonotic threats.
Keywords: Spillover; Zoonotic diseases; Wild animals; Virus; Mutations; Prevention; Zoonotic spillover; Viral mutations; Bushmeat; Vaccine gap